Factors Affecting Satisfaction Regarding Maternity Services Among Postnatal Mothers in a Tertiary Hospital of Kathmandu - Parajuli, Puspa; Paudel, Narayani (Journal of Nobel Medical College, 2019)
Background: Maternal satisfaction towards care provided during pregnancy, childbirth and puerperium is one of the key outcome measures for quality of care. In order to provide satisfactory maternity services health workers should focus on mother-friendly care. Various factors may affect on mothers' satisfaction regarding maternity services.The objective of this study was to assess the factors affecting satisfaction regarding maternity services among postnatal mothers.Materials and Methods: A descriptive, cross-sectional study was conducted in postnatal ward of Kathmandu Medical College Teaching Hospital. A total of 180 postnatal mothers were purposively selected for the study. Ethical clearance was obtained from the institutional review committee of Kathmandu Medical College. Face to face interview technique was used to collect the data using pre – designed structured questionnaire. Data collection was done from June to July 2019. Data were analysed using Statistical Package for Social Science 20.0 version. Both descriptive and inferential statistics were used for data analysis.Results: Majority (83.9%) of the mothers were satisfied with overall maternity services. The level of satisfaction was higher in (82.8%) environmental factor, (80%) health care delivery system of hospital and (73.3%) communication. There was significant association between sexes of current child with maternal satisfaction.  Mothers having current child male were more satisfied with maternity services provided by the hospital (COR: 4.90 with 95% CI: 1.97, 12.18).Conclusion: The study concluded that majority of postnatal mothers were satisfied with maternity services provided at hospital. Current child male was significantly associated with satisfaction level of mothers on maternity services.